Proceedings of the 5th International Workshop on Green and Sustainable Software 2016
DOI: 10.1145/2896967.2896968
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the Java collection framework on overall energy consumption

Abstract: Abstract-This paper presents a detailed study of the energy consumption of the different Java Collection Framework (JFC) implementations. For each method of an implementation in this framework, we present its energy consumption when handling different amounts of data. Knowing the greenest methods for each implementation, we present an energy optimization approach for Java programs: based on calls to JFC methods in the source code of a program, we select the greenest implementation. Finally, we present prelimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 31 publications
2
55
0
Order By: Relevance
“…In recent years, awareness within society of the significant side-effects of energy demands has grown, acknowledging the need for sustainable software development [1]. In fact, software developments are keen on developing energy-efficient software [2], and a long list of (mostly recent) efforts that include [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15] has tried to provide developers with the libraries, tools, techniques and data to support energy-aware development. Even considering these efforts, the green computing research area is still at an early stage where research issues, challenges and opportunities abound [16], [17], [18].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, awareness within society of the significant side-effects of energy demands has grown, acknowledging the need for sustainable software development [1]. In fact, software developments are keen on developing energy-efficient software [2], and a long list of (mostly recent) efforts that include [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15] has tried to provide developers with the libraries, tools, techniques and data to support energy-aware development. Even considering these efforts, the green computing research area is still at an early stage where research issues, challenges and opportunities abound [16], [17], [18].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, this is a recent and intensive area of research where several techniques to analyze and optimize the energy consumption of software systems are being developed. Such techniques already provide knowledge on the energy efficiency of data structures [15,27] and android language [25], the energy impact of different programming practices both in mobile [18,22,31] and desktop applications [26,32], the energy efficiency of applications within the same scope [2,17], or even on how to predict energy consumption in several software systems [4,14], among several other works.…”
mentioning
confidence: 99%
“…Microsoft acknowledged that as a software bug, "Based on our investigations we can confirm that it is not an issue with the battery cells, and we believe this is something that can be addressed via software" [29]. Research has shown that energy efficiency can be improved significantly with minor code optimization [44,22,30,44,13,47].…”
Section: Introductionmentioning
confidence: 66%